Analisis Pemetaan Daerah Rawan Banjir dan Strategi Mitigasi untuk Masyarakat Kabupaten Luwu - Hasrin, Sri Wahyuni; Mat Rasul (Fakultas Ilmu Sosial dan Hukum, 2024)
Flooding is a natural disaster that often hits Indonesia with a detrimental impact, especially for the community, the loss can be in the form of loss of life and material. This research focuses on mapping flood-prone areas in Luwu Regency based on the Spatial Overlay Analysis method based on geographic information system (GIS) and formulating effective mitigation strategies for the people of Luwu Regency. based on the Spatial Overlay Analysis method based on geographic information system (GIS). There are 3 variables used in this research, namely Soil Type, Slope and Rainfall. The mapping results show that some areas in Luwu Regency have a high level of flood vulnerability. The implementation of this mitigation strategy is expected to reduce the risk and impact of flooding and increase community resilience to flood disasters in the future.